An Islamic Law Sociology Review on Menre’ Bola Baru Tradition in Bugis Community - Alim Mappiasse, Achmad Habibul Alim; Achmad, Mukhsin (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2024)
Menre’ Bola Baru or moving to a new house is a local Bugis culture. The focus of this research is that among the Bugis tribe, especially South Sulawesi, there are differences of opinion regarding the Menre’ Bola Baru tradition because some rituals are considered deviating from Islamic teachings, so it is necessary to know the sociology of Islamic law. This research aims to further review the Menre’ Bola Baru tradition as a tradition of the Bugis community according to the Sociology of Islamic Law. The research uses a library research approach by adopting a descriptive-qualitative method. The research data sources come from interviews and secondary data, which the author gets from journals, books and observation results. While the research data analysis adopted the Miles and Huberman analysis technique, which was carried out by reducing data, presenting data and drawing conclusions. This research found that the Menre’ Bola Baru ceremony inherited from the ancestors of the Bugis tribe has a series of stages that contain local wisdom values so that these traditional activities or ceremonies still exist today. Meanwhile, Menre’ Bola Baru in the review of Islamic Law Sociologists experiences a combination of Islamic law and customs to become a religious practice. The role of religion is indeed very important as a source of values adopted by the community as a benchmark for action. Thus, religion determines the social structure of a society.